Political decentralization and taxes in the 1991 Charter (2021)
In any form of State, the territorial entities have the possibility of establishing the elements of one or more taxes (generating event, taxable base, active and passive subjects, and tariff). These can be previously determined by law, which would be the most genuine form of political decentralization; However, in Colombia, by constitutional provision of 1886 to date, the tax competition between the Nation and the territorial entities has been decided in favor of the former. Bypassing in this way two possibilities of political decentralization that the current Constitution establishes through taxes. However, the first with roots in 1886; the second with source in 1991, and by political omission of the Congress and tacit consent of the Constitutional Court, as soon as the respective organic law of territorial ordering that allows it has not been properly issued. This situation that encourages the Nation to continue to maintain its preeminence, almost 150 years old, in the political-tax issue.